MERIT SYSTEM DALAM MANAJEMEN PEGAWAI NEGERI SIPIL - Arief Daryanto (Jurnal Manajemen Kepegawaian, 2007)
Government officials in Indonesia are required to continuously improve their services quantitatively and qualitatively to increase the country competitiveness and public sector management quality. Common stereotype about low government official performance implies that they are not yet capable of proliferating their productivity. Working motivation is needed to produce high working spirit to provide excellent service to the community. A system which can generate high working motivation based on result oriented organizational values and fair and accurate merit system performance evaluation are required. This paper is aimed at opening the thinking paradigm about merit system in managing government officials to increase their productivity, quantitatively and qualitatively. Keywords: Merit System, Civil Service (PNS), Competitiveness, Performance Appraisal, Competency, Merit Pay